2017
DOI: 10.1016/j.agee.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation gradient and crop management affect N2O emissions: Simulation of mitigation strategies in rainfed Mediterranean conditions

Abstract: In Mediterranean areas high precipitation variability and crop dependence on soil water availability make the interaction between climate and agricultural management a key issue for mitigating N2O emissions. In this study we used the STICS model to capture the effect of a water deficit gradient and precipitation variability on N2O emissions and mitigation strategies (i.e. N fertilizer type, grain legumes introduction in crop rotations and crop residues management) in a rainfed Mediterranean transect (HWD-Senés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 43 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…The emission of N2O associated to denitrification is then calculated as a variable fraction of the denitrification rate depending on pH and WFPS. A more detailed description of N2O emission simulation by STICS can be found in Plaza-Bonilla et al (2017). Independent data from the two datasets obtained were used to calibrate the model.…”
Section: Overview Of the Stics Soil-crop Model And Its Evaluation Formentioning
confidence: 99%
See 1 more Smart Citation
“…The emission of N2O associated to denitrification is then calculated as a variable fraction of the denitrification rate depending on pH and WFPS. A more detailed description of N2O emission simulation by STICS can be found in Plaza-Bonilla et al (2017). Independent data from the two datasets obtained were used to calibrate the model.…”
Section: Overview Of the Stics Soil-crop Model And Its Evaluation Formentioning
confidence: 99%
“…Rainfed Mediterranean agroecosystems are characterized by the low magnitude and high variability of precipitation and the high evapotranspiration rates, severely limiting crop yield potential. In these areas, winter cereals show a good adaptation given the partial synchrony of their water needs with the distribution of precipitation and the key contribution of the soil water recharge period (Lampurlanés et al, 2016;Plaza-Bonilla et al, 2017). In different rainfed Mediterranean areas of Spain reduced and no-tillage (NT) systems have been introduced during the last three decades aimed to reduce costs and mitigate soil erosion (Moreno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture can also mitigate the GHG balance via carbon (C) sequestration (Smith et al., ). Agronomic practices can be improved by generating more C residues via higher biomass production, which sequesters more C in the soil (Collins, Rasmussen, & Douglas, ), and by improving N management to reduce N 2 O emissions (Plaza‐Bonilla, Léonard, Peyrard, Mary, & Justes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Justes, Mary, and Nicolardot (2009) parameterized the decomposition module and demonstrated that the model predicts crop residue decomposition well, including that of fresh cover crop residues for a wide range of C:N ratio. The model was also determined to simulate correctly many effects of cover crops on nitrate leaching, soil C dynamics and CO 2 emissions, soil N 2 O emissions, and water and temperature stress on plants (Constantin, Beaudoin, Launay, Duval, & Mary, 2012;Plaza-Bonilla et al, 2017;Vuichard et al, 2016). Constantin et al (2012) shown that STICS was satisfactory for predicting long-term N mineralization from cover crops based on 13-17 years of experimental data from three contrasted pedoclimatic sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation